2008
DOI: 10.1007/s11146-008-9106-6
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Investment and the Turn-of-the-Month Effect: Evidence from REITs

Abstract: Institutional investment, REITs, Calendar effect, Preferred habitat, Window dressing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…This is confirmed by Connors et al (2002) for the period 1994‐1999 and further confirmed by Compton et al (2006) for the period 1999‐2003. More recently, Wiley and Zumpano (2009, p. 199) conclude that the turn‐of‐the‐month effect “[…] does not appear to diminish over time” for a US REIT during the period 1980‐2004. The presence of the enhanced international turn‐of‐the‐month effect in stock indices is also well documented in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by Connors et al (2002) for the period 1994‐1999 and further confirmed by Compton et al (2006) for the period 1999‐2003. More recently, Wiley and Zumpano (2009, p. 199) conclude that the turn‐of‐the‐month effect “[…] does not appear to diminish over time” for a US REIT during the period 1980‐2004. The presence of the enhanced international turn‐of‐the‐month effect in stock indices is also well documented in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This question has been addressed in a variety of ways. One way, as is the case with this paper, focuses on calendar anomalies such as the January effect (Lee and Lee, 2003), the turn-of-the-month effect (Wiley and Zumpano, 2009) and the Monday effect (Friday and Higgins, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, B-shares are open to 1 For earlier documented evidence of 'intra-month' or 'turn-of-the-year' effects in one or more international markets, see Ariel (1987Ariel ( , 1988, Lakonishok and Smidt (1989), Cadsby and Ratner (1992), Agrawal and Tandon (1994), Wong (1995), Hensel and Ziemba (1996) and Kunkel et al (2003). There is also evidence of such effects in the US Real Estate Investment Trust (REIT) market (Wiley and Zumpano, 2009) and American Depositary Receipt (ADR) arenas (Bouges et al, 2009). 2 Dzhabarov and Ziemba (2010) show that the US 'turn-of-the-month' effect is partially reflected in futures prices ahead of time.…”
Section: Market Background and Indices Examinedmentioning
confidence: 99%
“…They relate their findings to institutional investors who increased their investments in REITs during this period. Recently, Wiley and Zumpano (2009) have shown that the turn-of-the-month anomaly for US REITs did not diminish over time during the period of 1980 to 2004.…”
Section: Systematic Equity Return Patterns 63mentioning
confidence: 99%